The Role of Government in Addressing the Social and Economic Impacts on Natural Disaster Victims in Padang Pariaman Regency (A Case Study of Flood and Landslide Disasters in Padang Pariaman Regency) - Fitri, Sintya; Putri, Nora Eka (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The main objective of this study is to analyze the role of the government in addressing the social and economic impacts experienced by victims of floods and landslides in Padang Pariaman Regency. This research is motivated by the frequent occurrence of geological disasters such as floods and landslides, which cause significant losses, as well as the suboptimal post-disaster social and economic recovery efforts by the local government. This study employs a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. Informants include representatives from the Regional Disaster Management Agency (BPBD), Social Affairs Office, local village governments (nagari), community leaders, and affected residents from three selected nagari: Katapiang, Tapakih, and Sungai Durian. Komaruddin's theory of role is used to analyze the findings through four indicators: task execution, behavioral patterns, function implementation, and involvement. The results reveal that the government's role remains focused on emergency response efforts, such as the distribution of food aid and basic necessities, while long-term recovery actions—such as economic rehabilitation and social reconstruction—have not been optimally implemented. Factors hindering social and economic recovery include budget limitations, inter-agency coordination issues, and the absence of an integrated strategy based on community needs. This study highlights the urgency of enhancing the effectiveness of government roles in the post-disaster phase to ensure the sustainability of the affected community's social and economic life.